Multipronged Understandings of Teacher Wellbeing: School Teachers Lived Experiences in Nepal - Devkota, Kamal Raj (Education and Development, 2025)
This study unfolds how the teachers’ professional, psychological, cognitive, emotional, economic and social experiences intersect in shaping their overall wellbeing. Based on the review of the educational policies and the analysis of the data derived from the survey and the interviews and focus group discussions with the teachers of the schools of Nepal, this study reveals that some complex intersectionality exists among the multipronged dimensions of the teacher wellbeing. The review of the policy documents shows that the recent policies have still not explicitly articulated the issues of teacher well-being, job satisfaction, and job attrition yet. Although there exists inconsistency between the results of the quantitative survey and the narratives from the interviews and the group discussions, the analysis reveals that the teachers are experiencing dissatisfaction in their professional learning and job security. The study suggests that the emerging concerns of teacher wellbeing need to be addressed in both educational policies and practices. Else, it may lead the country to a massive shortage of qualified, competent and dedicated teachers who can contribute to promotion of the quality of education.